Instability of Tn5 inserts in cyanobacterial cloning vectors. - Gendel, S M (1987)
Transposon Tn5 was used to produce random insertions in two hybrid cloning vectors for the unicellular cyanobacterium Anacystis nidulans. The transposon-containing plasmids were used to localize essential replication functions and to characterize the stability of large inserts in these vectors. The effect of the insertions on plasmid function was tested by transformation into a derivative of A. nidulans that had been cured of the endogenous plasmid used to construct the vectors. A region of approximately 4 kilobases was essential for successful plasmid transformation and replication. This region has also been shown to be involved in plasmid replication by deletion analysis. High rates of excision of Tn5 inserts within this region and restoration of normal replication function were observed when transformants were selected by using a resistance marker outside the replication region in the absence of selection for the transposon-coded kanamycin resistance. Transposon inserts outside this region were not deleted.